Modeling of depth variable 3D time-lapse seismic noise based on measured noise at the CO2CRC Otway project - Alajmi, M.; Bona, Andrej; Pevzner, Roman (SEG, 2013)
Non-repeatable noise in seismic time-lapse poses one of the big challenges of 4D seismic analysis. We propose to construct a variety of time-lapse noise models by matching the amplitude spectra (both temporal and spatial) in a running window to the real time-lapse noise while using random phase spectra. This ensures the preservation of the time dependent character of the noise while allows for rapid generation of many noise realizations. Such rapid time-lapse noise model construction is crucial in Monte Carlo type simulations of time changing seismic response, such as CO2 geosequestration. Herein, we apply the method to the CO2CRC Otway project time-lapse monitoring model.